Kondo resonance effects in emergent flat band materials - Ukpong, Aniekan Magnus (Frontiers in Physics, 2023)
Macroscopic degrees of freedom that are involved in the transport of carriers through mesoscopic electronic devices are susceptible to the effects of strong many-body correlations. The presence of magnetic impurities in dilute magnetic alloys typically allows for insights into the Kondo effect from the scattering of free carriers by localized electron states of the magnetic impurities but this effect is not well understood when there are no d-band electron states. Herein, the signatures of the Kondo resonance effect are elucidated in quantum dots derived from a carbon-nanoline embedded monolayer hexagonal boron nitride whose electron states host flat band ferromagnetism as distinct broken symmetry states. The Quantum transport state of mesoscopic devices modeled as quantum dots tunnel coupled to metallic leads is computed by direct diagonalization of the Hamiltonian. The possibility of realizing quantum dots with highly tunable electron states in energy interconversion devices is discussed to show the importance of screening effects on single-electron energy levels. The quantum master equation is solved within different formalisms to determine the stationary-state particle and energy currents. Stability diagrams are calculated to show the dependence of the conductance on experimental control variables of the quantum dot device. The computed responses of the stationary-state transport signatures are used to characterize Kondo resonance effects from flat band states of embedded carbon nanoline-based quantum dots. It is found that the local network structure of the hexagonal ring carbon cluster-based quantum dot has a broken particle–hole symmetry in the transport state. This signals the formation of the quasiparticle states expected in second-order scattering when the macroscopic “charge” pseudospin symmetry of the tunneling electron state is broken dynamically due to charging. The results are discussed to show the implications of a vanishing particle-hole symmetry in the carrier transport state of quantum dots for energy conversion applications.